Opportunities and challenges of redeveloping on-grade state highways: reflections on the role of service-learning in the SE 14th Street Corridor Project in Des Moines, IA - Roberts, Gage Alexander (Kansas State University, 2024)
Through the Federal Aid Highway Act of 1956, the United States Government routed highways directly and often intentionally through historically minoritized communities. Today, there are over 164,000 miles of highway in the United States, with many cities left dealing with the impacts of a large road cutting through the heart of their communities. One such highway is SE 14th Street in Des Moines, Iowa. This on-grade state highway serves as a stretch of US Route 69 and cuts through diverse communities on the SE side of Des Moines. In this report, I evaluate the opportunities and challenges of redeveloping on-grade state highways in cities. In addition, I also examine the impact of service-learning on the redevelopment of such corridors. I undertook this work through a focus on a semester-long service-learning project that focused on brownfield revisioning and redevelopment of the SE 14th Street Corridor in Des Moines, Iowa. Through a case study approach and ten semi-structured interviews with planners, economic developers, and other stakeholders in Des Moines, I provide recommendations on how to better plan for these communities through the use of critical service-learning. These recommendations include utilizing the high-traffic visibility of the corridor, investing in parks and trails, diversifying housing options, improving the uses and facades of the development along the corridor, and finding sparks for increased investment. I also present recommendations on how a critical service-learning approach to such projects may help prioritize the needs of historically marginalized communities and bring about social change.
Keywords: Highways; Des Moines, IA; Service-learning; Revitalization